2022
DOI: 10.3390/w14050793
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Apportionment of Potential Pollution Sources Using Multivariate Statistical Techniques and APCS-MLR Model to Assess Surface Water Quality in Imjin River Watershed, South Korea

Abstract: Reliable water quality monitoring data, identifying potential pollution sources, and quantifying the corresponding potential pollution source apportionment are essential for future water resource management and pollution control. Here, we collected water quality data from seven monitoring sites to identify spatiotemporal changes in surface water in the Imjin River Watershed (IRW), South Korea, distinguish potential pollution sources, and quantify the source apportionment from 2018–2020. An analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…A Pearson's correlation analysis was performed to determine which water quality parameters had a significant linear relationship. The correlation coefficient (r) value close to +1 and -1 indicates a strong positive and negative correlation between the two parameters (Cho et al, 2022). According to the values of the correlation coefficient, the interrelationship between the two parameters can be defined as follows:0.9-1; very high,0.7-0.89; high,0.5 -0.69; moderate,0.26-0.49; weak,0-0.…”
Section: Discussionmentioning
confidence: 99%
“…A Pearson's correlation analysis was performed to determine which water quality parameters had a significant linear relationship. The correlation coefficient (r) value close to +1 and -1 indicates a strong positive and negative correlation between the two parameters (Cho et al, 2022). According to the values of the correlation coefficient, the interrelationship between the two parameters can be defined as follows:0.9-1; very high,0.7-0.89; high,0.5 -0.69; moderate,0.26-0.49; weak,0-0.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, livestock breeding lacks proper management of process wastes (animal carcasses, feathers, feed, and manure), which also increases the risk of non-point source pollution. In previous studies of surface-water pollution sources, aquaculture was often ignored and not particularly discussed (Cho et al 2022, Zhang et al 2020a, Zhang et al 2009). However, through eld surveys during the study period, it was observed that shery workers drain and dredge shponds in the winter before the Chinese Spring Festival.…”
Section: Cold-season Pollution Source Analysismentioning
confidence: 99%
“…As a result of industrialization, urbanization, increase in population size and over-exploitation, the quality of the world's water supply has declined significantly in recent decades. [1][2][3][4][5] The main sources of water pollution are agricultural run-off, sanitary waste and, most importantly, industrial discharges. A wide range of harmful chemicals and compounds, including dyes, [6][7][8] pesticides, [9][10][11] heavy metals, [12][13][14] endocrine disruptors, 15,16 etc., have recently been found in toxic concentrations in drinking water around the world.…”
Section: Introductionmentioning
confidence: 99%